Comparative biochemical characterization of the monoacylglycerol lipase inhibitor KML29 in brain, spinal cord, liver, spleen, fat and muscle tissue. (April 2015) - Pasquarelli, Noemi; Porazik, Christoph; Hanselmann, Johannes; Weydt, Patrick; Ferger, Boris; Witting, Anke
Abstract: Monoacylglycerol lipase (MAGL) is part of the endocannabinoid and the prostaglandin signaling system. MAGL degrades the endocannabinoid 2-arachidonoylglycerol (2-AG) into glycerol and arachidonic acid. MAGL-induced arachidonic acid is the primary source for prostaglandin synthesis in the brain. 2-AG mainly induces neuroprotective and anti-inflammatory effects, whereas prostaglandins are related to pro-inflammatory effects inducing neurotoxicity. Therefore, inhibition of MAGL represents a promising target for neurological diseases characterized by inflammation. However, as 2-AG is an agonist for the cannabinoid receptor 1 (CB1 ), inhibition of MAGL might be associated with unwanted cannabimimetic effects. Here, we show that oral administration of KML29, a highly selective inhibitor of MAGL, induced large and dose-dependent changes in 2-AG levels in vivo in brain and spinal cord of mice. Of note, MAGL inhibition by KML29 induced a decrease in prostaglandin levels in brain and most peripheral tissues but not in the spinal cord. MAGL expression was highest in fat, liver and brain, whereas the cytosolic phospholipase A2 (cPLA2 ), a further enzyme responsible for arachidonic acid production, was highly expressed in spinal cord, muscle and spleen. In addition, high doses (10 mg/kg) of KML29 induced some cannabimimetic effects in vivo in the tetrad test, including hypothermia, analgesia and hypomotility without induction of cataleptic behavior. In summary, inhibition of MAGL by KML29 represents a promising strategy for targeting the cannabinoid and prostaglandin system of the brain with only a moderate induction of cannabimimetic effects. Highlights: MAGL inhibition by KML29 mostly increased 2-AG levels in brain, spinal cord and fat. KML29 is selective for MAGL. KML29 induced a decrease in prostaglandins in brain and most peripheral tissues. MAGL and cPLA2 have a complementary expression pattern. KML29 induced some cannabimimetic effects without producing cataleptic behavior.